Serological study of Crimean – Congo haemorrhagic fever in Sheep in Thi – Qar province - H. T, Haneen; Ateya, Hekmet k.; Abed, Nabeel M. (South Eastern European Journal of Public Health, 2024)
Crimean Congo hemorrhagic fever virus (CCHFV) causes a lethal tick – borne zoonotic disease with severe clinical manifestation in humans but does not produce symptomatic disease in wild or domestic animals. It is endemic in a large region of the word. One of the main indicators that the disease is endemic in a region is the presence of antibodies specific to CCHFV in animal populations. The factors contributing to differential outcomes of infection between species are not understood. Serological studies have shown sheep are important to the survival of CCHFV in nature. Nevertheless, need for more studies on this subject in Iraq. Blood samples were taken from 200 sheep of different sex, variable age and physiological status. Only 100 samples used for physiological testes while 186 used for Microbiological test (ELISA) test. The present study was appeared a high level about (144)78.53% of positive carrier sheep while negative samples (42)21.46% in Thi – Qar province which include different regions such as Al-eakihah , Al- rifai and Al- garma region which recorded about 92.85% , 90% and 90 % respectively comparative with another region of thi qar province that appear low level of infected such as Al-fadhliya , Al-tar and Al- manar which recorded about 75%, 50% and 60.71% respectively. The current study focused on and attempted to connect the different physiological states, sex and age with infected animals. The male sex appears ahigh level of infected about 83.92% comparative with female was appeared low level of infected by CCHF virus about 74.61%, while recorded high infected in non – pregnant about 75% comparative with pregnant about 73,80 . Also, the present study was showed ahigh level of infected in age from 5 to nine years about 82.4% comparative with another age ranges which appeared about 71.11, 78.50 %.